2022
DOI: 10.1155/2022/7971415
|View full text |Cite
|
Sign up to set email alerts
|

Value Research of NLR, PLR, and RDW in Prognostic Assessment of Patients with Colorectal Cancer

Abstract: Objective. This study aimed to investigate the relevance of the study with the neutrophil count and lymphocyte count ratio (NLR), platelet count and lymphocyte count ratio (PLR), and red blood cell distribution width (RDW) in the prognostic evaluation of colorectal cancer patients. Methods. 143 patients with colorectal cancer from January 2016 to January 2019 were selected by our hospital, and then, other 143 cases of physical examiners as normal groups were selecting to proceed colonoscopic biopsy to diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR), have been investigated in several disease states, e.g. solid tumours, systemic lupus erythematosus, coronary artery disease, retinal artery occlusion, chronic kidney disease and stable COPD [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR), have been investigated in several disease states, e.g. solid tumours, systemic lupus erythematosus, coronary artery disease, retinal artery occlusion, chronic kidney disease and stable COPD [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 76 studies were found in the databases, including 25 studies in the PubMed, 50 studies in the Embase and 1 study in the Cochrane Library. Finally, seven studies ( 23 26 , 31 33 ) were included for final analysis. The flow chart of the study selection was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies had reported the relationship between RDW and the prognosis of CRC ( 23 26 , 31 33 ). Zhang X et al ( 23 ) reported that elevated RDW could be an independent factor for non-metastatic rectal cancer; Cheng KC et al ( 37 ) analyzed 5,315 CRC patients and did propensity score matching analysis, they found that RDW was a predictor of OS, DFS and CSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, many risk factors and prognostic variables were identi ed, including tumor markers, histological type, tumor location, platelet count [4], and tumor-node-metastasis(TNM) staging system. These factors are related to the prognosis of colorectal tumors [5].…”
Section: Introductionmentioning
confidence: 99%